Reactivity and catalytic activity of hydrogen atom chemisorbed silver clusters - Manzoor, Dar; Pal, Sourav (Journal of Physical Chemistry A, 2015)
Metal clusters of silver have attracted recent interest of researchers as a result of their potential in different,catalytic applications and low Cost. However, due to the completely filled d orbital and very high first ionization potential of the silver atom, the silver-based catalysts interact very weakly with the reacting molecules. In the current work, density functional theory calculations were carried out to investigate the effect of hydrogen atom chemisorption. On the reactivity and catalytic properties of inert silver clusters Our results affirm that the hydrogen atom chemisorption leads to enhancement the binding energy of the adsorbed O-2 molecule on the inert silver clusters. The increase in the binding energy is also characterized by the decrease in the Ag-O and increase in the O-O bond lengths in the case of the AgnH Silver clusters. Pertinent to the increase in the O-O bond length, a. significant red shift in the O-O Stretching frequency is. also noted in the case,of the AgnH silver clusters. Moreover, the hydrogen atom chemisorbed silver clusters show low reaction barriers and heat Of formation of the final products for the,environmentally important CO oxidation reaction as compared to the parent catalytically inactive clusters The obtained results were compared with those of the corresponding gold and hydrogen atom chemisorbed gold clusters obtained at the same level of theory. It is expected the current computational study will provide key insights for future advances in the design of efficient nanosilver-based catalysts through the adsorption of a small atom or a ligand.